The future role of MFCs in biomass energy - Ieropoulos, Ioannis; Greenman, John (Frontiers in Energy Research, 2023)
Microbial fuel cells (MFC) are an emerging green technology which offers several comparative advantages over other technologies for utilizing biomass. It is a technology that treats (cleans) wet organic waste, converting chemical energy to electricity in order to energise its peripheral, control systems and produce excess electrical power. The main advantage is the technology’s ability to utilise wet biomass in suspension or in solution (i.e., too wet to burn) and change the biomass directly into bioenergy in the form of electricity. All other technologies either combust the biomass directly (e.g., wood fuel) or change the biomass into refined fuels which are then combusted or fed to chemical fuel cells to generate heat or electricity. Excluding methane production from biomass, and fermentation leading to hydrogen production, all other biomass/biofuel technologies utilize dry plant matter, which mainly consists of cellulose or lignocellulose and they cannot directly utilize sludge or slurries of organic detritus material. The substrates used for MFCs are not traditionally made into organic fuels, as with other biomass technologies, but are used directly as fuel, recasting the “waste” suspensions and solutions, and elevating them into the category of being fuels themselves. To a stack of MFCs, a polluted river, landfill leachate or farmland run-off, can all be reassigned as fuel. This wet fuel is widespread around the planet, the amounts found and the energy contained within can be colossal, and the cost as a fuel is close to zero. This review gives a general overview of biomass energy along with extraction techniques and compares advantages and disadvantages of MFCs with other biomass technologies for producing electrical energy.